Two-dimensional readout in a liquid xenon ionisation chamber - Solovov, V. (2002)
A two-dimensional readout with metal strips deposited on both sides of a glass plate is investigated aiming to assess the possibility of its use in a liquid xenon ionisation chamber for positron emission tomography. Here, we present results obtained with an [alpha]-source. It is shown that position resolution of [less-than-or-equals, slant]1 mm, fwhm, can be achieved for free charge depositions equivalent to those due to [gamma]-rays with energy from 220 down to 110 keV.